Core Fucosylation of the T Cell Receptor Is Required for T Cell Activation - Liang, Wei; Mao, Shanshan; Sun, Shijie; Li, Ming; Li, Zhi; Yu, Rui; Ma, Tonghui; Gu, Jianguo; Zhang, Jianing; Taniguchi, Naoyuki; Li, Wenzhe (Frontiers in Immunology, 2018)
CD4+ T cell activation promotes the pathogenic process of systemic lupus erythematosus (SLE). T cell receptor (TCR) complex are highly core fucosylated glycoproteins, which play important roles in T cell activation. In the present study, we found that the core fucosylation of CD4+ T cells was significantly increased in SLE patients. Loss of core fucosyltransferase (Fut8), the sole enzyme for catalyzing the core fucosylation of N-glycan, significantly reduced CD4+ T cell activation and ameliorated the EAE-induced syndrome in Fut8-/- mice. T cell activation with OVA323-339 loaded major histocompatibility complex II (pMHC-II) on B cell was dramatically attenuated in Fut8-/-OT-II CD4+ T cells compared with Fut8+/+OT-II CD4+ T cells. Moreover, the phosphorylation of ZAP-70 was significantly reduced in Fut8+/+OT-II CD4+ T cells by the treatment of fucosidase. Our results suggest that core fucosylation is required for efficient TCR-pMHC-II contacts in CD4+ T cell activation, and hyper core fucosylation may serve as a potential novel biomarker in the sera from SLE patients.